Towards sustainable energy: Factors affecting solar power system adoption by small and medium-sized businesses - Atchike, Desire Wade; Zhenyu, Zhao; Ali, Tausif; Weishang, Guo; Jabeen, Gul (Frontiers in Environmental Science, 2022)
Climate change mitigation is the prime priority of businesses in the modern world, making them inclined to opt for clean energy acceptance. From the end-user perspective, acceptance of novel technologies is inevitably vital in promoting such technologies, and certain factors could play an influential role in shaping the acceptance behavior of businesses in embracing those technologies. Against this background, the purpose of this study is to determine the factors that influence the acceptance of solar panel systems (SPS) by small and medium businesses (SMBs) in Pakistan. A questionnaire survey was conducted in seven districts of Pakistan's Punjab province from December 2021 to February 2022. The data were collected using a Five-point Likert scale. Based on the questionnaire survey, the variance-based structural equation model technique is utilized. The outcomes are: (a) size of the business, ease of using SPS, and credibility of SPS are the top three driving forces. (b) The cost of SPS, and the pressure of competitors are the bottlenecks to the acceptance of SPS, while the absence of technical skills is a neutral factor. (c) According to the effect size and path coefficients, the cost of SPS, and the size of the business are found to be the most significant factors, while the absence of technical skills is found to have less significance. As it is found that economic incentives majorly affect the acceptance of SPS thus, it is concluded that lowering the cost of SPS will increase its acceptance. Based on empirical results, it is suggested to promote public awareness about the environmentally-friendly nature of solar power systems to improve its acceptability at the individual as well as firm levels.